Coating agents, laminates, packaging materials

By using a coating agent composed of vinyl alcohol-based polymer and polyalkyleneimine on an olefin-based substrate, a gas barrier coating is formed, and the adhesion of polyvinyl alcohol and ethylene vinyl alcohol on an olefin-based substrate is solved. The problem of insufficient properties has achieved efficient gas sealing effect.

CN116635230BActive Publication Date: 2024-12-17DIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180077177.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-10
Filing Date
2021-12-02
Publication Date
2024-12-17
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

Polyvinyl alcohol and ethylene vinyl alcohol have low adhesion on olefin-based substrates, making it difficult to effectively prevent the penetration of oxygen and other gases.

Method used

A coating agent containing a vinyl alcohol-based polymer and a polyalkylene imine is used to form a gas barrier coating by spraying or other coating methods to improve the adhesion and gas barrier properties of the olefin-based substrate.

Benefits of technology

It achieves high adhesion and gas barrier properties for olefin-based substrates, significantly improves the sealing effect of oxygen and other gases, and is suitable for sealing applications of packaging materials and electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004230698450000081
    Figure BDA0004230698450000081
  • Figure BDA0004230698450000151
    Figure BDA0004230698450000151
  • Figure BDA0004230698450000152
    Figure BDA0004230698450000152
Patent Text Reader

Abstract

The present invention provides a coating agent for imparting gas barrier properties, which has excellent adhesion to various substrates including olefin-based substrates, a laminate having excellent gas barrier properties obtained by using the coating agent, and a packaging material. A coating agent comprising a resin (A) and an aqueous solvent (B), wherein the resin (A) comprises a vinyl alcohol polymer (A1) and a polyalkyleneimine (A2), a laminate having a gas barrier coating formed by the coating agent, and a packaging material formed by the laminate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating agent, a laminate obtained by using the coating agent, and a packaging material. Background Art

[0002] Gas barrier materials are used in various fields for the purpose of preventing the intrusion of gases such as moisture and oxygen from the outside air. For example, packaging materials used in the packaging of food, beverages, etc., in order to protect the contents from various circulation, storage such as refrigeration, heat sterilization and other treatments, and long-term storage of food, require oxygen barrier properties, carbon dioxide barrier properties, and barrier properties to various aroma components to prevent the intrusion of oxygen from the outside in order to inhibit oxidation. In addition, various displays such as solar cells, liquid crystals, organic or inorganic electroluminescence (hereinafter referred to as "EL"), and electronic devices such as electronic paper usually use glass substrates as sealing materials for protecting their internal structures and blocking oxygen and water vapor from the outside, but for the purpose of providing thin, lightweight, or flexible products, the use of transparent gas barrier films based on plastic films is being gradually studied. (For example, refer to patent documents 1 and 2).

[0003] As a means for imparting gas barrier properties to a plastic film, there is known a method of applying a coating agent using polyvinyl alcohol, ethylene vinyl alcohol, or the like (Patent Document 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-077553

[0007] Patent Document 2: Japanese Patent Application Publication No. 2010-253861

[0008] Patent Document 3: Japanese Patent Application Publication No. 2017-115076 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, although polyvinyl alcohol and ethylene vinyl alcohol are excellent in gas barrier properties, their adhesion to olefin-based substrates such as polyethylene and polypropylene is extremely low.

[0011] Means for solving problems

[0012] The present invention has been made to solve at least a part of the above problems, and an object of the present invention is to provide a gas barrier coating agent having excellent adhesion to an olefin-based substrate, and a laminate and a packaging material obtained by using the coating agent.

[0013] Effects of the Invention

[0014] According to the present invention, a gas barrier coating agent having excellent adhesion to various substrates including olefin-based substrates can be provided. DETAILED DESCRIPTION

[0015] <Coating agent>

[0016] The coating agent of the present invention comprises a resin (A) and an aqueous solvent (B), wherein the resin comprises a vinyl alcohol polymer (A1) and a polyalkylene imine (A2) as essential components. The coating agent of the present invention is described in detail below.

[0017] (Vinyl alcohol polymer (A1))

[0018] As the vinyl alcohol polymer (A1), a hydrolyzate (A1-1) of a homopolymer or copolymer of a vinyl ester (a1) and any one obtained by a known conventional method can be used. Alternatively, as the vinyl alcohol polymer (A1), a reaction product (A1-2) of a hydrolyzate of a homopolymer or copolymer of a vinyl ester (a1) and an aldehyde and any one obtained by a known conventional method can be used.

[0019] Examples of the vinyl ester (a1) include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl octanoate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, and the like, and one or more thereof may be used alone or in combination. Preferably, vinyl acetate is used.

[0020] Examples of the polymerizable compound (a2) copolymerizable with the vinyl ester (a1) include ethylene, propylene, 1-butene, isobutylene, 1,3-butadiene, isopropenyl acetate, 2-propenyl acetate, styrene, α-methylstyrene, vinyl chloride, acrylonitrile, maleic anhydride, methyl acrylate, methyl methacrylate, N-vinyl-N-methylformamide, vinylacetamide, N-vinylformamide, N-(hydroxymethyl)-N-vinylformamide, hydroxyethyl acrylate, methyl vinyl ketone, and diacetone acrylamide, and one or more thereof may be used alone or in combination. Among them, ethylene, isopropenyl acetate, and 2-propenyl acetate are preferably used.

[0021] When vinyl ester (a1) and polymerizable compound (a2) are used in combination, their usage amounts can be appropriately adjusted. From the viewpoint of gas barrier properties, the amount of polymerizable compound (a2) is preferably limited to less than 60 mol %, more preferably less than 25 mol %, of the total amount of vinyl ester (a1) and polymerizable compound (a2).

[0022] The degree of polymerization of the vinyl ester polymer as a precursor of the vinyl alcohol polymer (A1-1) or (A-2) is not particularly limited, but is, for example, 500 to 10,000, more preferably 800 to 6,000, and even more preferably 1,000 to 3,000. This allows a coating agent having an excellent balance between gas barrier properties and coating suitability.

[0023] Examples of the aldehyde used in the acetalization include aliphatic aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, octanal, and dodecylaldehyde; alicyclic aldehydes such as cyclohexanecarboxaldehyde; aromatic aldehydes such as benzaldehyde, naphthaldehyde, anthracenecarboxaldehyde, phenylacetaldehyde, tolualdehyde, dimethylbenzaldehyde, cuminaldehyde, and benzylaldehyde; unsaturated aldehydes such as cyclohexenal, dimethylcyclohexenal, and acrolein; aldehydes having a heterocyclic ring such as furfural and 5-methylfurfural; hemiacetals such as glucose and glucosamine; aldehydes having an amino group such as 4-aminobutyraldehyde, and the like. In addition, aliphatic ketones such as 2-propanone, methyl ethyl ketone, 3-pentanone, and 2-hexanone; aliphatic alicyclic ketones such as cyclopentanone and cyclohexanone; and aromatic ketones such as acetophenone and benzophenone can be used alone or in combination of two or more.

[0024] As the acid catalyst used in the acetalization, conventionally known organic acids and inorganic acids such as acetic acid, p-toluenesulfonic acid, nitric acid, sulfuric acid and hydrochloric acid can be used.

[0025] Suitable specific examples of the vinyl alcohol polymer (A1) include polyvinyl alcohol, ethylene vinyl alcohol, polyvinyl butyral, etc. One type may be used alone, or two or more types may be used in combination. From the viewpoint of the balance between gas barrier properties and adhesion, it is more preferred to use any one of polyvinyl alcohol and ethylene vinyl alcohol, or to use both.

[0026] The degree of saponification of the vinyl alcohol polymer (A1-1) is preferably 90% or more, preferably 95% or more, from the viewpoint of excellent gas barrier properties. It may also be 100%. The degree of saponification can be measured by FTIR using, for example, a Nicolet 5700 FTIR spectrometer controlled by OMNIC software.

[0027] The vinyl alcohol polymer (A1-2) is preferably one obtained by acetalizing a precursor having a saponification degree of 95% or more.

[0028] (Polyalkyleneimine (A2))

[0029] The polyalkyleneimine (A2) is a resin having a polyalkyleneimine skeleton, which is obtained by polymerizing one or more of alkyleneimines (e.g., ethyleneimine, propyleneimine) by a conventional method. By using the vinyl alcohol polymer (A1) and the polyalkyleneimine (A2) in combination, the gas barrier properties of the coating agent can be maintained and the adhesion to the olefin substrate can be improved.

[0030] The polyalkyleneimine (A2) may be a linear polyalkyleneimine formed by a linear polyalkyleneimine chain, or a branched polyalkyleneimine having a branched polyalkyleneimine chain. Examples of the polyalkyleneimine (A2) include polyethyleneimine and polypropyleneimine. The polyalkyleneimine (A2) may be a substance in which a substituent (e.g., hydroxypropyl, hydroxyethyl) is introduced into at least a portion of the nitrogen atoms of the polyalkyleneimine chain. A substance modified with an organic metal compound such as tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, tetramethyl titanate, polyhydroxystearate titanium, diacetylacetonate titanium, tetraacetylacetonate titanium, polyacetylacetonate titanium, octanediolate titanium, ethyl acetoacetate titanium, lactate titanium, triethanolamine titanium, and stearate titanium may be used, and two or more polyalkyleneimines may be used in combination.

[0031] It is believed that polyalkylene imine (A2) has amino groups (NHR groups, NH 2 The polyalkylene imine (A2) preferably contains branched polyalkylene imine because it is effective in improving the adhesion. The degree of branching of the polyalkylene imine (A2) can be represented by the ratio of the primary amino group, the secondary amino group and the tertiary amino group possessed by the polyalkylene imine (A2). It can be appropriately adjusted according to the vinyl alcohol polymer (A1) used and its blending amount. As an example, it is preferred to use a polyalkylene imine (A2) having a primary amino group ratio of 20 to 40%, a secondary amino group ratio of 30 to 60% and a tertiary amino group ratio of 20 to 35%. The ratio of the primary amino group, the secondary amino group and the tertiary amino group contained in the polyalkylene imine (A2) can be adjusted using 13 The branched polyalkylene imine is preferably a branched polyethylene imine.

[0032] From the aspect of excellent adhesion, the number average molecular weight of polyalkylene imine (A2) is preferably 5,000 or more, more preferably 9,000 or more, and further preferably 50,000 or more. There is no particular limitation on the upper limit, but as an example, it is 100,000 or less. The number average molecular weight of polyalkylene imine (A2) is the number average molecular weight obtained by measuring pullulan as a standard substance by GPC (gel permeation chromatography) method.

[0033] In the coating agent of the present invention, the amount of polyalkylene imine (A2) is preferably 1% by mass or more and 90% by mass or less of the total amount of vinyl alcohol polymer (A1) and polyalkylene imine (A2). Thus, the gas barrier properties of the coating agent of the present invention can be maintained, and the adhesion to olefin substrates can be more reliably improved. More preferably, it is 10% by mass or more and 50% by mass or less. In the case where the coating agent of the present invention does not contain polyalkylene imine (A2), the adhesion to olefin substrates is insufficient. In the case where vinyl alcohol polymer (A1) is not contained (in the case where resin (A) is formed only by polyalkylene imine (A2)), the coating film has adhesiveness and is not suitable for post-processing.

[0034] The coating agent of the present invention may include resins (A3) other than vinyl alcohol polymers (A1) and polyalkylene imines (A2). As such resins (A3), for example, vinyl resins such as homopolymers or copolymers of cellulose resins, polyesters, polyurethanes, olefins, and styrene, acrylic resins, epoxy resins, amide resins, natural rubbers, and their complexes (such as core-shell resins) can be cited, and one or more of them can be used in combination. If the amount of resin (A3) is too much, the gas barrier properties are sometimes reduced, so the amount of resin (A3) is preferably limited to less than 10% by mass of resin (A) (the total amount of vinyl alcohol polymers (A1), polyalkylene imines (A2), and resin (A3)). More preferably, less than 5% by mass, more preferably less than 1% by mass. It can also be 0% by mass.

[0035] The amount of the resin (A) contained in the coating agent of the present invention can be appropriately adjusted according to coating suitability and the like.

[0036] (Aqueous solvent (B))

[0037] As the aqueous solvent (B), water, a water-soluble organic solvent dissolved in water, etc. can be used. As water, pure water such as ion exchange water, ultrafiltration water, reverse osmosis water, distilled water, or ultrapure water can be used. In order to prevent the generation of mold or bacteria, from the viewpoint of long-term storage, it is preferred to use water sterilized by ultraviolet irradiation or addition of hydrogen peroxide.

[0038] Examples of the water-soluble organic solvent include glycols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, polyethylene glycol, and polypropylene glycol; glycols such as butanediol, pentanediol, and hexanediol; glycol esters such as propylene glycol laurate; diethylene glycol ethers such as diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, and carbitol; glycol ethers such as cellosolves including propylene glycol ether, dipropylene glycol ether, and triethylene glycol ether; alcohols such as methanol, ethanol, isopropanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butanol, and pentanol; lactones such as sulfolane, esters, ketones, and γ-butyrolactone, lactams such as N-(2-hydroxyethyl)pyrrolidone, glycerol, and polyalkylene oxide adducts thereof, and other various solvents known as aqueous organic solvents. These aqueous organic solvents can be used alone or in combination of two or more.

[0039] (Additive (C))

[0040] The coating agent of the present invention may further contain an additive (C) in addition to the resin (A) and the aqueous solvent (B). Examples of the additive (C) include layered inorganic compounds, crosslinking agents capable of reacting with the functional groups of the vinyl alcohol polymer (A1) and the polyalkylene imine (A2), inorganic fillers, defoamers, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, etc.), plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, leveling agents, etc.

[0041] As the layered inorganic compound, natural montmorillonite, synthetic montmorillonite, natural mica, synthetic mica, hydrotalcite and talc represented by montmorillonite, etc., and oleophilic treated montmorillonite and oleophilic synthetic mica obtained by organic treatment thereof can be cited. By using the layered inorganic compound, the gas barrier property of the coating agent is improved, but there is a tendency that the adhesion to the olefin-based substrate is reduced. When the amount of the layered inorganic compound is 10 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the resin (A), the balance between the gas barrier property and the adhesion is excellent, which is preferred.

[0042] Examples of the crosslinking agent include aldehydes such as formalin and glutaraldehyde; acetals such as diacetals of glutaraldehyde; aliphatic polyisocyanates represented by hexamethylene diisocyanate or its derivatives (adducts, urate forms, biuret forms, etc.), aromatic aliphatic polyisocyanates represented by xylylene diisocyanate or its derivatives, aromatic polyisocyanates represented by toluene diisocyanate or its derivatives, and carbamic acids which are reaction products of these isocyanates with polyols. Isocyanates such as ester prepolymers; epoxies; organic metal compounds of titanium, silicon, aluminum, zirconium, boron, etc. and alkoxides; methylol ureas such as methylol urea and methylol melamine; carboxyl-containing polymers such as polyacrylic acid polymers and maleic anhydride polymers; carbodiimides such as p-phenylene-bis(2,6-xylylcarbodiimide), tetramethylene-bis(tert-butylcarbodiimide), and cyclohexane-1,4-bis(methylene-tert-butylcarbodiimide); boric acid; titanium lactate, etc. Isocyanates may be blocked isocyanates obtained by using a known blocking agent, or emulsion-type isocyanates may be used.

[0043] The use of a crosslinking agent improves adhesion to olefin-based substrates, but tends to reduce gas barrier properties. When the amount of the crosslinking agent is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the resin (A), the balance between gas barrier properties and adhesion is excellent, which is preferred.

[0044] <Laminated body>

[0045] The laminate of the present invention is obtained by coating the coating agent of the present invention on a substrate and drying it. It should be noted that the dried coating film of the coating agent of the present invention is also referred to as a gas barrier coating below. There are no particular restrictions on the substrate to which the coating agent of the present invention can be applied, and examples include polyethylene terephthalate (PET) film, polystyrene film, polyamide film, polyacrylonitrile film, polyethylene film (OPE: biaxially stretched polyethylene film, LLDPE: low-density polyethylene film, HDPE: high-density polyethylene film), polypropylene film (CPP: unstretched polypropylene film, OPP: biaxially stretched polypropylene film) and other polyolefin films, polyvinyl alcohol films, ethylene-vinyl alcohol copolymer films, etc.

[0046] In addition, films formed by laminating inorganic vapor-deposited layers of metals such as aluminum, silicon dioxide, and metal oxides such as aluminum oxide on these films may also be used. Specific films include OPP films, PET films, LLDPE films, CPP films with aluminum vapor-deposited layers, OPP films, PET films, nylon films with silicon dioxide vapor-deposited layers, and OPP films, PET films, nylon films with aluminum oxide vapor-deposited layers. The coating agent of the present invention has excellent adhesion to these substrates including polyolefin films, and can improve the gas barrier properties of the substrate and the aroma retention properties of various flavor components.

[0047] The coating method of the coating agent of the present invention is not particularly limited, and spray coating, spin coating, dipping, roller coating, blade coating, blade roll method, blade method, curtain coating method, slit coating method, screen printing method, inkjet method, dispensing method, die coating (die coating) method, direct gravure method, reverse gravure method, flexographic method, blade coating method, dot coating method, etc. can be used.

[0048] The thickness of the gas barrier coating can be appropriately adjusted according to the type of substrate and the desired gas barrier property, and is, for example, 0.2 μm to 2.0 μm. If the film thickness is too thin, the gas barrier property cannot be improved, and if it is too thick, the adhesion may be reduced.

[0049] The laminate with the gas barrier coating may also be further bonded to other substrates using an adhesive. Alternatively, other substrates may be laminated on the laminate with the gas barrier coating by an extrusion method. As other substrates, the same substrates as described above may be used. As an adhesive, for example, a solvent-based or solvent-free adhesive of a two-component curing urethane system commonly used for bonding films may be used. The adhesive preferably uses an adhesive having an aromatic ring concentration of 0.5 mmol / g or more and 7.0 mmol / g or less of the cured coating film. From the perspective of a laminate with excellent gas barrier properties, an adhesive of 3.5 mmol / g or more and 7.0 mmol / g or less is more preferably used.

[0050] The aromatic ring concentration of the adhesive is the value obtained by dividing the total equivalent (Y) of the monomers having aromatic rings in the total equivalent (X) of the monomers used in the synthesis of the polyol composition and polyisocyanate composition mixed in the adhesive by the total solid content mass (Z) of the adhesive. When a monomer (y) having x aromatic rings in one molecule is used to prepare a polyol composition or a polyisocyanate composition, when calculating the total equivalent (Y) of the monomer, the equivalent of the monomer (y) is x times. For example, the adhesive 1 used in the examples described below is mixed with the polyol composition 1 and the polyisocyanate composition 1 in a solid content mass ratio of 1:1. Therefore, its aromatic ring concentration is 2.2 mmol / g according to the following formula.

[0051] [Mathematical formula 1]

[0052]

[0053] The laminate of the present invention may further have a printing layer. The printing layer is formed at any position of the laminate by various printing inks such as gravure ink, flexographic ink, offset ink, stencil ink, and inkjet ink, and by a conventional printing method used in printing on polymer films. These inks may be a single component type or a two-component type used in combination with a curing agent such as isocyanate.

[0054] As an example of a specific embodiment of the laminated body of the present invention, the following can be mentioned:

[0055] (1) Substrate / gas barrier coating / printing layer / adhesive layer / sealing layer

[0056] (2) Substrate / printing layer / gas barrier coating / sealing layer

[0057] (3) Substrate / gas barrier coating / printing layer / gas barrier coating / sealing layer

[0058] (4) Substrate / gas barrier coating / printing layer / adhesive layer / inorganic vapor deposition layer / sealing layer

[0059] (5) Substrate / inorganic vapor deposition layer / gas barrier coating / printing layer / adhesive layer / sealing layer

[0060] (6) substrate / printing layer / adhesive layer / substrate / inorganic vapor-deposited layer / gas barrier coating / adhesive layer / sealing layer, etc., but not limited thereto.

[0061] Since the gas barrier coating has excellent adhesion to the olefin substrate, as the substrate of the composition examples (1) to (4), OPP film, OPE film, PET film, nylon and other polyamide films can be used. As the sealing layer, LLDPE film, CPP film can be used, and as the sealing layer having an inorganic vapor-deposited layer, aluminum vapor-deposited LLDPE film, aluminum vapor-deposited CPP film can be used.

[0062] Since the gas barrier coating also has excellent adhesion to the inorganic vapor-deposited layer, the configurations of (5) and (6) are also preferred. As a substrate having an inorganic vapor-deposited layer in the configuration (5), an OPP film having an aluminum oxide vapor-deposited layer can be cited. As a substrate having an inorganic vapor-deposited layer in the configuration (6), an aluminum vapor-deposited OPP film can be cited. In any of the configuration examples, if an OPP film or an OPE film (or a film on which inorganic vapor deposition is performed) is used as the substrate, it becomes a laminate with excellent reusability, and therefore is preferred.

[0063] <Packaging materials>

[0064] The packaging material of the present invention is obtained by using the laminate of the present invention, making the faces of the sealing films of the laminate overlap relatively, and then heat-sealing the peripheral ends thereof. As a bag-making method, the following method can be cited: the laminate of the present invention is bent or overlapped so that the faces of its inner layer (the faces of the sealing films) are opposite, and the peripheral ends thereof are heat-sealed according to forms such as side sealing type, two-side sealing type, three-side sealing type, four-side sealing type, envelope-fitting sealing type, palm-fitting sealing type, pleated sealing type, flat bottom sealing type, square bottom sealing type, gusseted type, other heat-sealing types, etc. The packaging material of the present invention can take various forms according to the contents, use environment, and use form. It can also be a self-supporting packaging material (self-supporting bag), etc. As a heat-sealing method, it can be carried out by known methods such as rod sealing, rotary roller sealing, belt sealing, impulse sealing, high-frequency sealing, and ultrasonic sealing.

[0065] In the packaging material of the present invention, after the contents are filled from the opening, the opening is heat-sealed to manufacture a product using the packaging material of the present invention. Examples of the filled contents include rice desserts, bean desserts, nuts, biscuits / cookies, pancake desserts, fruit jelly, pies, half-cooked cakes, candies, snacks and other desserts, bread, crisp noodles, instant noodles, dry noodles, pasta, aseptically packaged rice, vegetable porridge, porridge, packaged rice cakes, cereal foods and other food products, pickles, boiled beans, natto, miso, frozen tofu, tofu, nameko mushrooms, konjac, wild vegetable processed products, jams, peanut butter, salads, frozen vegetables, potato processed products and other agricultural processed products, ham, bacon, sausages, chicken processed products, beef canned products and other livestock products. Aquatic products such as fish ham / sausage, aquatic products, fish cakes, seaweed, salted seafood, dried bonito, salted fish, smoked salmon, wasabi cod roe, peach, orange, pineapple, apple, pear, cherry, corn, asparagus, mushroom, onion, carrot, white radish, potato, frozen side dishes represented by hamburger steak, meatball, fried aquatic products, dumplings, croquettes, etc., refrigerated side dishes, etc., pre-prepared foods, butter, margarine, cheese, cream, instant creamer, infant formula milk powder, etc., liquid seasoning, steamed curry, pet food, etc. In addition, the packaging material of the present invention can also be used as packaging material for pharmaceuticals such as cigarettes, disposable pocket warmers, infusion bags, cosmetics, vacuum insulation materials, etc.

[0066] Example

[0067] Hereinafter, specific synthesis examples and embodiments are listed to further illustrate the present invention, but the present invention is not limited to these embodiments. It should be noted that, in the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0068] <Preparation of coating agent>

[0069] (Examples 1-20)

[0070] In a reaction vessel equipped with a stirrer, a nitrogen inlet pipe, and a reflux condenser, a vinyl alcohol polymer (A1) and ion exchange water were added, and the mixture was slowly heated to 90°C and stirred for 4 hours to dissolve the vinyl alcohol polymer (A), and then cooled to room temperature to obtain an aqueous solution of the vinyl alcohol polymer (A1). An aqueous solution of polyalkylene imine (A2), water, and isopropanol were added thereto so that the solid content of the resin (A) was 5% by mass and the water / IPA ratio was 7 / 3, thereby obtaining the coating agent of Example 1-14. It should be noted that the mixing ratio (solid content) of the vinyl alcohol polymer (A1) and the polyalkylene imine (A2) in Example 1-20 is shown in Table 1-4.

[0071] (Comparative Examples 1-3)

[0072] Except that the polyalkyleneimine (A2) was not used, the same procedure as in the examples was carried out to obtain coating agents of Comparative Examples 1 and 2. Except that the vinyl alcohol polymer (A1) was not used, the same procedure as in the examples was carried out to obtain a coating agent of Comparative Example 3.

[0073] The vinyl alcohol polymer (A1) and the polyalkylene imine (A2) used in Examples and Comparative Examples are as follows.

[0074] (Vinyl alcohol polymer (A1-1))

[0075] Polyvinyl alcohol, degree of polymerization: 2400, degree of saponification: more than 98%

[0076] (Vinyl alcohol polymer (A1-2))

[0077] Polyvinyl alcohol, degree of polymerization: 1700, degree of saponification: more than 98%

[0078] (Vinyl alcohol polymer (A1-3))

[0079] Polyvinyl butyral, degree of polymerization: 600, degree of acetalization: 10%

[0080] (Vinyl alcohol polymer (A1-4))

[0081] Exceval AQ-4104 (manufactured by Kuraray Co., Ltd.) was used.

[0082] (Polyalkyleneimine (A2-1)

[0083] Polyethyleneimine, number average molecular weight: 70,000, primary amino group: 25%, secondary amino group: 50%, tertiary amino group: 25%

[0084] (Polyalkyleneimine (A2-2))

[0085] Polyethyleneimine, number average molecular weight: 100,000, primary amino group: 31%, secondary amino group: 41%, tertiary amino group: 28%

[0086] <Preparation of adhesive>

[0087] (Adhesive 1)

[0088] (Preparation of polyol composition 1)

[0089] A mixture of 25.0 parts of Coronate T-80 (a toluene diisocyanate made by Tosoh Corporation, consisting of 80% of 2,4-isomer and 20% of 2,6-isomer), 35.3 parts of ACTCOL D-1000 (a bifunctional polypropylene glycol with an average molecular weight of 1000 made by Mitsui Chemicals, Inc.), and 36.1 parts of ACTCOL D-400 (a bifunctional polypropylene glycol with an average molecular weight of 400 made by Mitsui Chemicals, Inc.) was heated to 100°C and stirred for 4 hours to react. At this time, the NCO content was 1.6%. Stirring was stopped, 42.9 parts of ethyl acetate was added thereto, stirring was started again to dissolve, and the temperature was lowered to 50°C. 3.6 parts of diethanolamine was added thereto, the temperature was raised to 75°C by heat generation, and maintained for 2 hours. The solid content hydroxyl value was 37.4 (mgKOH / g), and the non-volatile content was 70.7%.

[0090] (Preparation of polyisocyanate composition 1)

[0091] A mixture of 12.3 parts of 4,4'-diphenylmethane diisocyanate, 20.8 parts of ACTCOL D-1000, 14.5 parts of ACTCOL D-700 (Mitsui Chemicals, Inc., bifunctional polypropylene glycol with an average molecular weight of 700), and 22.6 parts of ethyl acetate was heated to 80°C and stirred for 4 hours, and then 22.4 parts of trimethylolpropane adduct of toluene diisocyanate was added. The nonvolatile content was 70.3%, and the NCO% (solution) was 4.5%.

[0092] (Preparation of Adhesive 1)

[0093] The polyol composition 1 and the polyisocyanate composition 1 prepared above were mixed at a solid content mass ratio of 1:1, and diluted with ethyl acetate to prepare an adhesive 1. The aromatic ring concentration of the adhesive 1 was 2.2 mmol / g.

[0094] (Adhesive 2)

[0095] (Preparation of polyol composition 2)

[0096] 879.37 parts of ethylene glycol, 1580.52 parts of phthalic anhydride and 0.10 parts of titanium tetraisopropoxide were added to a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a Snyder tube and a condenser, and the mixture was slowly heated so that the temperature of the upper part of the distillation tube did not exceed 100° C., and the internal temperature was maintained at 200° C. The esterification reaction was terminated when the acid value became 5.0 mgKOH / g or less, and a polyester polyol having a designed functional group number N=2 and a hydroxyl value=125 was obtained.

[0097] (Preparation of polyisocyanate composition 2)

[0098] 36 parts of 4,4-diphenylmethane diisocyanate and 19 parts of 2,4'-diphenylmethane diisocyanate were placed in a reaction vessel equipped with a stirrer, a thermometer, and a nitrogen inlet tube, stirred under nitrogen, and heated to 60°C. 11 parts of polypropylene glycol (hereinafter referred to as "PPG") with a number average molecular weight of 400, 22 parts of PPG with a number average molecular weight of 1000, and 11 parts of PPG with a number average molecular weight of 2000 were added dropwise several times, and stirred for 5 to 6 hours to complete the urethanization reaction. The NCO group content of the obtained polyisocyanate was 13.5%.

[0099] (Preparation of Adhesive 2)

[0100] The polyol composition 2 and the polyisocyanate composition 2 prepared above were mixed at a solid content mass ratio of 1:1, and diluted with ethyl acetate to prepare an adhesive 2. The aromatic ring concentration of the adhesive 2 was 4.5 mmol / g.

[0101] <Manufacturing of laminated body>

[0102] (Example 1-17, Comparative Example 1-3)

[0103] The coating agent prepared in the examples and comparative examples was applied to an OPP film (manufactured by Toyobo Co., Ltd., P2161), and dried for 1 minute in a hot air dryer set at 80°C to form a gas barrier coating. Next, adhesive 1 or 2 was applied to the barrier coating, and after the dilution solvent was volatilized in a dryer set at 50°C, a CPP film (manufactured by Toyobo Co., Ltd., P1128) was laminated. After aging at 40°C for 3 days, a laminate for evaluation was obtained (composition example 1: OPP film / gas barrier coating / adhesive layer / CPP film).

[0104] The film thickness of the gas barrier coating is shown in Table 1-4. The coating amount of the adhesive is 2.5 g / m 2(Solid content). In Example 8, a gas barrier coating was formed by blending 10 parts by mass of a water-dispersible polyisocyanate (Duranate WB40-100 manufactured by Asahi Kasei Corporation) with respect to 100 parts by mass of the solid content of the vinyl alcohol polymer (A1) and the polyalkylene imine (A2). In Example 12, a gas barrier coating was formed by blending 10 parts by mass of a filler (KUNIPIA-F manufactured by KUNIMINE INDUSTRIES) with respect to 100 parts by mass of the solid content of the vinyl alcohol polymer (A1) and the polyalkylene imine (A2).

[0105] (Examples 18 and 19)

[0106] The coating agent prepared with the formulation shown in Table 4 was applied to a 25 μm thick MDOPE film (manufactured by Tokyo Ink Co., Ltd., HIBLON PE25), and dried in a hot air dryer set at 80°C for 1 minute to form a gas barrier coating. Next, the adhesive 1 was applied to the barrier coating, and after the dilution solvent was volatilized in a dryer set at 50°C, a 60 μm thick LLDPE film (manufactured by Mitsui Chemicals Tocello Co., Ltd., TUX-HC) was attached. The film was aged at 40°C for 3 days to obtain a laminate for evaluation (Constitution Example 2: MDOPE film / gas barrier coating / adhesive layer / LLDPE film).

[0107] (Example 20)

[0108] The coating agent prepared with the formulation shown in Table 4 was applied to a BOPE film with a film thickness of 25 μm, and dried in a hot air dryer set at 80°C for 1 minute to form a gas barrier coating. Next, the adhesive 1 was applied to the barrier coating, and after the dilution solvent was volatilized in a dryer set at a temperature of 50°C, it was laminated to a LLDPE film with a film thickness of 60 μm (TUX-HC manufactured by Mitsui Chemicals Tocello Co., Ltd.). The film was aged at 40°C for 3 days to obtain a laminate for evaluation (Constitution Example 3: BOPE film / gas barrier coating / adhesive layer / LLDPE film).

[0109] (Reference example)

[0110] A laminate (Configuration Example 4: OPP film / adhesive layer / CPP film) was produced in the same manner as in Examples and Comparative Examples except that the gas barrier coating layer was omitted.

[0111] <Evaluation>

[0112] (Oxygen barrier)

[0113] The laminate after aging was adjusted to a size of 10 cm×10 cm, and the oxygen permeability (unit: cc / m) was measured in an atmosphere of 23° C. and 0% RH using OX-TRAN2 / 21 (manufactured by MOCON Co., Ltd.: oxygen permeability measuring device) in accordance with JIS-K7126 (isobaric method). 2 ·day·atm). It should be noted that RH stands for humidity. The results were evaluated according to the following 5 levels and summarized in Tables 1-4.

[0114] 5: less than 5

[0115] 4: 5 or more and less than 10

[0116] 3: 10 or more and less than 100

[0117] 2: 100 or more and less than 300

[0118] 1:300 and above

[0119] (Adhesion)

[0120] The adhesive strength of the laminate (unit: N / 15 mm) was measured by a 180° peeling method using a tensile tester at 25°C and a peeling speed of 300 mm / min. The results were evaluated according to the following four levels, which are summarized in Tables 1-4. It should be noted that in any case of the examples and comparative examples, peeling occurred at the interface between the gas barrier coating and the OPP film.

[0121] 4: 2.0 or above

[0122] 3: 1.5 or more and less than 2.0

[0123] 2: 1.0 or more and less than 1.5

[0124] 1: less than 1.0 [Table 1]

[0125]

[0126] [Table 2]

[0127]

[0128] [Table 3]

[0129]

[0130] [Table 4]

[0131]

[0132] [Table 5]

[0133]

[0134] Tables 1 to 5 show that the coating agent of the present invention has an excellent balance between gas barrier properties and adhesion to olefin substrates. On the other hand, the coating agent containing only the vinyl alcohol polymer (A1) or the polyalkyleneimine (A2) has insufficient adhesion to olefin substrates.

Claims

1. A laminate, It is characterized in that At least a substrate, a gas barrier coating, an adhesive layer and another substrate are provided in this order. The laminate does not contain a metal vapor-deposited layer, The substrate is the same as or different from the other substrates, The gas barrier coating is a dry coating film of a coating agent comprising a resin A and an aqueous solvent B, wherein the resin A comprises a vinyl alcohol polymer A1 and a polyalkylene imine A2. The polyalkylene imine A2 is a polyalkylene imine having a primary amino group ratio of 20 to 40%, a secondary amino group ratio of 30 to 60%, and a tertiary amino group ratio of 20 to 35%. The number average molecular weight of the polyalkyleneimine A2 is 5000 or more and 100000 or less, The amount of the polyalkyleneimine A2 in the coating agent is 1% by mass or more and 50% by mass or less of the total amount of the vinyl alcohol polymer A1 and the polyalkyleneimine A2. The adhesive layer is a layer of a two-component curable urethane-based solvent-based or solvent-free adhesive, and the aromatic ring concentration of the cured coating film of the adhesive layer is greater than or equal to 0.5 mmol / g and less than or equal to 7.0 mmol / g.

2. The laminate according to claim 1, in, The amount of the polyalkyleneimine A2 contained in the coating agent is 10% by mass or more and 50% by mass or less of the total amount of the vinyl alcohol polymer A1 and the polyalkyleneimine A2.

3. The laminate according to claim 1 or 2, in, The substrate and / or the other substrate is an olefin substrate. A packaging material comprising the laminate according to claim 1.

Citation Information

Patent Citations

  • Optical filter using gas barrier type film and organic el display

    JP2005077553A

  • Transparent gas barrier film

    JP2010253861A

  • Coating agent for barrier

    JP2017115076A

  • Resin composition for gas-barrier adhesive, adhesive, and laminate

    CN111065703A

  • Polyolefin film with barrier property

    JP1996245816A